(untitled) (GEON Journal (Management, Organizations and Business), 2018)
n this issue on management issues we refer to the importance of the strategy and the selection of personnel and a model to train staff, as well as an experience of ISO 9001, entertainment and marketing in children, and for young people their financial situation in University. There is a document on food security and sovereignty, tax reform and how ICTs develop skills in solving problems.